Tri-tert-butanolamine as an organic promoter in nucleophilic fluorination - Shinde, Sandip S.; Khonde, Nilesh; Kumar, P. (ChemistrySelect, 2017)
Tri-tert-butanol amine acts as promoter with alkali metal salts in the nucleophilic fluorination of alkylsulfonates. It significantly enhances the reactivity of alkali metal salts with minimum formation of side-products (alkene, ether, and alcohol) com-pared to other catalysts in fluorination reaction. The synergism of tert-alcohol and amine moiety plays a pivotal role in fluorination.